Preliminary studies on maleated polyethylene-octene elastomer modified polyamide 6 / polypropylene (70:30) nanocomposites - Othman, Norhayani; Hassan, Azman; Wahit, Mat Uzir; Rahmat, Abdul Razak (2006)
Rubber toughened nanocomposites consisting of polyamide 6 (PA6) and polypropylene (PP) matrix (70:30) with a maleated polyethylene-octene elastomer (POEgMAH) and organophilic modified montmorillonite (MMT) were prepared by melt compounding in a co-rotating twin-screw extruder followed by injection moulding. The POEgMAH content was varied in the range of 0 wt% - 20 wt% and the weight fraction of organoclay was fixed at 4 wt %. Mechanical properties of the blends were investigated by tensile, flexural and Izod impact testing. X-ray diffraction (XRD) was used to characterise the nanocomposites. Izod impact measurements indicated that the addition of POEgMAH led to a significant improvement in the impact strength of the PA6/PP nanocomposites. The impact strength increased up to more than twice enhancement after addition of 15wt% POEgMAH into PA6/PP nanocomposites. However, the tensile and flexural properties were found to decrease with increasing concentration of POEgMAH. XRD revealed that an intercalation organoclay silicate layer structure was formed in rubber toughened PA6/PP nanocomposites.